Pemanfaatan Tangki Riak untuk Mengukur Kecepatan Rambat Gelombang Permukaan Air - Taj Rosyidah; Eka Cahya Prima; Riandi Riandi (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2023)
The study intends to investigate the relationship between wavelength and frequency to calculate the speed of propagating waves on the water's surface. The researchers used a ripple tank to collect data by recording the pendulum's movement as well as the image of the ripples on the water's surface. The data is then analyzed with the Tracker application. The wavelength is determined by analyzing the recorded ripple shadows with the Tracker application. The Tracker application is used to analyze the recorded pendulum movement to obtain data on the period of vibration and calculate the frequency of the vibrations. The average surface wave velocity at a pendulum length of 10 cm is 3.38 10-2 m/s. In addition, for a 30 cm pendulum length, an average surface wave speed of 3.26 10-2 m/s is obtained.